The effects of absorber attachment location on vibration response of simply supported plate - Mohamed Salleh, Muhammad; Zaman, Izzuddin (Asian Research Publishing Network (ARPN), 2016)
Vibration analysis of thin walled structure has been an active research in engineering fields. This paper proposed to investigate the application of vibration absorber (VA) attached to the simply supported plate (SSP) in order to suppress the structural vibration. Two major factors influence on vibration reduction of late are investigated in term of the attachment location of vibration absorber and the number of absorber applied on structural dynamic of the plate. Finite element software of ANSYS APDL was performed to measure the dynamic response of plate. The results found that the best positioning vibration absorber are at the location of 0.35 m of x-axis and 0.40 m of y-axis which can attenuate the vibration along the frequency band. Numerical result also presented that when attached multiple absorber, the vibration reduction of plate provide larger suppression to SSP which average reduction almost 80% over the frequency modes. This study conclude that right position and number of absorber can be the major contribute to suppress vibration on a plate structure more effectively.